From Dispersed Urban Areas to Territories- in-between - Alexander Wandl (A+BE: Architecture and the Built Environment)
The dissertation began with the observation that there is an increasing body of literature suggesting that the conventional idea of a gradual transition in spatial structure from urban to rural does not properly reflect contemporary patterns of urban development and their potential for sustainable development. Furthermore, it was argued that large parts of the urbanised areas of Europe are dispersed and that these are neglected in urban and spatial planning policies. Such areas tend to be labelled simply as sprawl, though there is little evidence about whether such dispersed development is more or less sustainable than other forms of urban development. Moreover, evidence points in the direction that large amounts of dispersed urban development ask for different planning instruments which reflect the complexity and network structure of theses specific settlement patterns.